Manufacturing method of window glass for vehicle with adherend

The method enhances adhesion between vehicle window glass adherends and adhesives by using plasma treatment and a two-step cleaning process with water and polar solvents, ensuring durability in harsh environments.

JP2025005529APending Publication Date: 2025-01-17AGC INC
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023105730
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

Existing vehicle window glass adherends experience insufficient adhesion in harsh environments, such as high temperature and humidity, necessitating improved adhesion methods.

Method used

A method involving dry treatment of the adherend's adhesive surface, followed by application of a cleaning solution containing water and a polar solvent, and subsequent removal of the liquid to enhance adhesion, which includes plasma treatment to introduce hydrophilic functional groups and a two-step cleaning process to eliminate a weak boundary layer.

Benefits of technology

The method achieves excellent adhesion between the adherend and adhesive, maintaining durability under harsh conditions, with high cohesive failure rates in destructive tests and improved adhesive strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025005529000001_ABST
    Figure 2025005529000001_ABST
Patent Text Reader

Abstract

To provide a manufacturing method of a window glass for a vehicle with an adherend which exhibits excellent adhesiveness of the adherend to an adhesive agent even under more severe environment.SOLUTION: In a manufacturing method of a window glass for a vehicle with an adherend, the adherend having a resin surface and the widow glass for the vehicle are bonded via an adhesive agent. The method includes the steps of drying the adhesive surface of the adherend, making cleaning fluid containing water and / or polar solvent adhere to the dried adhesive surface, removing the fluid on the adhesive surface, and disposing the adherend on the window glass for the vehicle via the adhesive agent.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a vehicle window glass having an adherend. [Background technology]

[0002] Conventionally, in vehicles such as automobiles, there has been known a vehicle window glass with an adherend, in which an adherend having a resin surface is adhered to glass via an adhesive. One example is a structure in which a bracket for mounting an in-vehicle device is adhered to the inner surface of a windshield via an adhesive.

[0003] In such a structure with an adherend, it is known that the surface of the adherend is treated to improve the adhesion between the adherend and the adhesive. For example, Patent Document 1 discloses a method of obtaining a laminate by wiping surface B obtained by dry-treating surface A of a plastic with a cleaning tool containing at least one selected from the group consisting of water and a polar solvent, and applying at least one selected from the group consisting of an adhesive and a primer. It is also disclosed that the laminate obtained by the disclosed method exhibits excellent adhesion. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2019-84520 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, even in the laminate described in Patent Document 1, the adhesion between the adherend and the adhesive may be insufficient in a severe environment, for example, a high-temperature and high-humidity environment. Therefore, there is a demand for further improvement in adhesion in a vehicle window glass with an adherend.

[0006] In view of the above, an object of one aspect of the present invention is to provide a method for manufacturing a vehicle window glass with an adherend, which exhibits excellent adhesion between the adherend and an adhesive even under harsh environments. [Means for solving the problem]

[0007] In order to solve the above-mentioned problems, one aspect of the present invention is a method for manufacturing a vehicle window glass with an adherend, in which an adherend having a resin surface and a vehicle window glass are bonded together via an adhesive, comprising: dry-treating an adhesive surface of the adherend; applying a cleaning liquid containing one or more of water and a polar solvent to the dry-treated adhesive surface; removing the liquid on the adhesive surface; and arranging the adherend on the vehicle window glass via the adhesive. Effect of the Invention

[0008] According to one aspect of the present invention, there is provided a method for producing a vehicle window glass with an adherend, which exhibits excellent adhesion between the adherend and an adhesive even under harsh environments. [Brief description of the drawings]

[0009] [Figure 1] 1 is a plan view of a vehicle window glass with an adherend according to an embodiment of the present invention. [Diagram 2] 2 is a cross-sectional view taken along line II in FIG. 1. [Diagram 3] FIG. 2 is a flow diagram of a manufacturing method according to one embodiment of the present invention. [Figure 4] FIG. 2 is a diagram for explaining the device and method of the splitting test used in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. In the drawings, the same or corresponding components are denoted by the same reference numerals, and the description thereof may be omitted.

[0011] [Vehicle window glass with substrate] Fig. 1 is a view of an example of a vehicle window glass 1 with an adherend produced by this embodiment, as viewed from the vehicle inner side. Fig. 2 shows a cross-sectional view taken along line II in Fig. 1. As shown in Figs. 1 and 2, an adherend 30 is bonded to a main surface of a vehicle window glass 10 via an adhesive 20. Figs. 1 and 2 show a bracket as the adherend 30, but the detailed shape of the bracket is omitted.

[0012] <Vehicle window glass> The vehicle window glass 10 used in this embodiment may be a window glass for an automobile. In the example shown in Fig. 1, the vehicle window glass 10 is a front windshield, but may be, for example, a rear windshield, a side windshield, a roof windshield, or the like.

[0013] The vehicle window glass 10 may be a glass plate such as soda lime silicate glass, aluminosilicate glass, borate glass, lithium aluminosilicate glass, or borosilicate glass. The method for forming the glass plate is not particularly limited, but for example, a float method is preferable. The glass plate may be unreinforced, or may be tempered glass that has been subjected to air-cooling tempering or chemical tempering treatment. Unreinforced glass is formed by forming molten glass into a plate shape and slowly cooling it. Tempered glass is formed by forming a compressive stress layer on the surface of unreinforced glass. When the tempered glass is air-cooled tempered glass, the glass surface may be strengthened by rapidly cooling a heated glass plate from a temperature near the softening point and generating a compressive stress on the glass surface due to the temperature difference between the glass surface and the inside of the glass. On the other hand, when the tempered glass is chemically tempered glass, the glass surface may be strengthened by generating a compressive stress on the glass surface by an ion exchange method or the like. In addition, the vehicle window glass is preferably transparent, but may be a glass plate that is colored to an extent that does not impair transparency. The shape of the glass sheet is not particularly limited to a rectangular shape, and may be processed into various shapes. The glass sheet used for the vehicle window glass may be bent and curved. Gravity forming, press forming, etc. are used as the bending forming.

[0014] The vehicle window glass 10 may be a single glass sheet made of the above-mentioned glass plate, or may be a laminated glass sheet as shown in Fig. 2. The laminated glass sheet is made by bonding a plurality of glass plates 11, 12 together with an interlayer film 13 interposed therebetween. The above-mentioned glass plates are also used for the plurality of glass plates used in the laminated glass.

[0015] In the laminated glass, the material of the interlayer film 13 disposed between the multiple glass plates 11 and 12 is not particularly limited, but is preferably a thermoplastic resin. Specific examples of the material of the interlayer film include thermoplastic resins such as plasticized polyvinyl acetal resins, plasticized polyvinyl chloride resins, saturated polyester resins, plasticized saturated polyester resins, polyurethane resins, plasticized polyurethane resins, ethylene-vinyl acetate copolymer resins, ethylene-ethyl acrylate copolymer resins, cycloolefin polymer resins, and ionomer resins. In addition, a resin composition containing a modified block copolymer hydrogenated product described in Japanese Patent No. 6065221 can also be preferably used. Among these, a plasticized polyvinyl acetal resin is preferably used because it has an excellent balance of various performances such as transparency, weather resistance, strength, adhesive strength, penetration resistance, impact energy absorption, moisture resistance, heat insulation, and sound insulation. The above thermoplastic resins may be used alone or in combination of two or more. The term "plasticized" in the plasticized polyvinyl acetal resin means that the resin is plasticized by adding a plasticizer. The same applies to other plasticized resins.

[0016] The intermediate film 13 may be a resin that does not contain a plasticizer, such as an ethylene-vinyl acetate copolymer resin. Examples of the polyvinyl acetal resin include polyvinyl formal resin obtained by reacting polyvinyl alcohol (PVA) with formaldehyde, polyvinyl acetal resin in the narrow sense obtained by reacting PVA with acetaldehyde, and polyvinyl butyral resin (PVB) obtained by reacting PVA with n-butylaldehyde. In particular, PVB is used as a suitable material because it has an excellent balance of various properties such as transparency, weather resistance, strength, adhesive strength, penetration resistance, impact energy absorption, moisture resistance, heat insulation, and sound insulation. The above resins may be used alone or in combination of two or more kinds.

[0017] When the vehicle window glass is a single-pane glass, its thickness may be 0.2 mm or more and 5 mm or less. When the vehicle window glass 10 is a laminated glass as shown in FIG. 2, the overall thickness of the vehicle window glass 10 (including the thickness of the interlayer film) may be 2.3 mm or more and 8 mm or less. The thickness of each of the multiple glass plates constituting the laminated glass may be 0.5 mm or more and 3.5 mm or less. The thicknesses of the multiple glass plates may be the same or different from each other. The thickness of the glass plate 12 on the vehicle exterior side may be 1.1 mm or more and 3.5 mm or less. The thickness of the glass plate 11 on the vehicle interior side may be 0.5 mm or more and 2.3 mm or less.

[0018] Furthermore, as shown in Figs. 1 and 2, the vehicle window glass 10 may have a shielding layer 15 formed on the periphery of the glass sheet 11 on the vehicle interior side. The shielding layer 15 is also called a black ceramic layer. The configuration of the shielding layer 15 is not particularly limited, but it is preferable that the shielding layer 15 is a layer formed by applying and firing a ceramic paste (glass paste) of a color such as black, gray, or dark brown. The shielding layer 15 has a function of protecting a sealant or the like for mounting and holding the vehicle window glass 10 on the vehicle body in the vehicle from ultraviolet rays and the like. In the example of Figs. 1 and 2, the adherend 30 is bonded to the shielding layer 15 via an adhesive 20. That is, the adhesive 20 is disposed between the adherend 30 and the shielding layer 15. By disposing the adherend 30 in the area where the shielding layer 15 is provided, the adherend 30 is hidden by the shielding layer 15 when viewed from outside the vehicle, improving aesthetics, and the adherend 30 can be prevented from being deteriorated by ultraviolet rays and the like. The shielding layer may be formed on the peripheral edge of the glass sheet 12 on the exterior side of the vehicle.

[0019] <Adherend> The adherend used in this embodiment is not particularly limited as long as it is bonded to the above-mentioned vehicle window glass via an adhesive. The adherend may be a support for mounting an on-vehicle device, specifically, a bracket for mounting an on-vehicle camera, an on-vehicle sensor (rain sensor, defrost sensor, temperature sensor, humidity sensor), etc., a mirror base for mounting an inner mirror, and may further be a molding, a protector, a temporary fixing pin, a clip, a holder, a hinge, etc. The method according to this embodiment is particularly suitable for bonding a bracket disposed on the main surface of the vehicle window glass among the above-mentioned adherends. The adherend is preferably a bracket for mounting an on-vehicle device.

[0020] The adherend may have a resin surface. "Having a resin surface" means that at least a part or the entire surface is made of resin. Thus, the adherend may be a molded body made entirely or partially of resin, or a molded body made of a material other than resin, the surface of which is partially or entirely covered with resin. At least the adhesive surface of the adherend may be made of resin. The adhesive surface of the adherend is a surface that can be opposed to the main surface of the vehicle window glass and aligned along the main surface. The adhesive surface may be flat, or may be curved to match the curve of the opposing surface of the vehicle window glass 10 (convex toward the outside of the vehicle).

[0021] Specific examples of resin materials used for the adherend include polyamides (PA) such as nylon 6 and nylon 6,6, high heat-resistant polyamides based on terephthalic acid or isophthalic acid (PA6T, PA6I, PA6T / 6I, etc.), polyimide (PI), polyetherimide (PEI), polyesters such as polybutylene terephthalate (PBT), polyethylene terephthalate (PET), polyolefins such as polyethylene (PE) and polypropylene (PP), polycarbonate (PC), acrylonitrile-butadiene-styrene (ABS), polyacetal (POM), polyvinyl chloride (PVC), and epoxy (EP). The resin materials may be the above homopolymers, or copolymers or polymer blends (polymer alloys) that combine one or more of the above. Among the above materials, polyamide, high heat-resistant polyamide, or polybutylene terephthalate are preferred because of their excellent chemical resistance and mechanical properties. Therefore, the resin material of the adherend used in this embodiment preferably contains or consists of one or more of polyamide, high heat resistant polyamide, and polybutylene terephthalate. Also, the resin of the adherend preferably contains one or more of polyamide, polyester, polyacetal, polycarbonate, modified polyphenylene ether, and epoxy.

[0022] The resin material may be a resin reinforced with a filler such as fibers or inorganic particles. As the reinforcing fibers, glass fibers, carbon fibers, etc. are preferable. As the fiber-reinforced resin, polybutylene terephthalate, polyetherimide, etc. reinforced with glass fibers are preferable. When the resin contains reinforcing fibers, the fibers may be contained in an amount of 5% by mass to 70% by mass, preferably 30% by mass to 50% by mass, based on the entire resin.

[0023] When the adherend is a resin molded body, the molding method is not limited. The adherend may be one molded from the above-mentioned resin material by a method such as injection molding, casting, extrusion molding, blow molding, etc. Also, the adherend may be one insert-molded using an insert material made of a material other than resin (metal, etc.).

[0024] When the adherend is a molded body made of a material other than resin, the surface of which is partially or entirely coated with resin, it may be, for example, an electrodeposition-coated body obtained by electrodeposition-coating a substrate made of metal or the like with an electrodeposition coating material containing a resin. The electrodeposition-coated body is formed by passing an electric current through a substrate in an electrolytic cell, precipitating resin coating particles on the substrate surface, and heating and curing the coating material in a curing oven to form a film. When forming a resin surface by electrodeposition coating, it is preferable that the electrodeposition coating material is a cationic electrodeposition coating material. The resin contained in the electrodeposition coating material may be a thermosetting resin such as an epoxy resin, and is preferably an epoxy resin modified with an amine or ammonium. On the other hand, the substrate may be a molded body made of metal, including steel, aluminum, etc., particularly a plate-shaped molded body. An example of an electrodeposition-coated body is a cationic electrodeposition-coated steel plate manufactured by Aoki Electric Industry Co., Ltd. (using an electroposition coating material made by Kansai Paint Co., Ltd., Elecron HG-305E Black). The resin coating can also be formed by applying a solution or dispersion containing a resin, or a molten resin, or the like, onto the substrate, or by adhering a preformed sheet-like resin layer, or by electroless plating, or the like.

[0025] <Adhesive> In this embodiment, the adhesive is not particularly limited, and adhesives such as moisture-curing, photo-curing, and thermosetting adhesives can be used. However, in terms of environmental load response and equipment introduction costs, those using a moisture-curing adhesive as the main agent are preferable, and those using a urethane adhesive, modified silicone adhesive, or the like as the main agent are preferable. The above-mentioned main agent may be used alone as the adhesive in this embodiment, but in addition to the above-mentioned main agent, auxiliary agents such as an adhesive strength improving component and a curing accelerating component may be used together. Examples of such auxiliary agents include silane compounds, polyol compounds, polyisocyanates, and the like. Among these, auxiliary agents that are also used as primers, such as silane coupling agents, are preferable. The above auxiliary agent may be contained in the main agent in advance in an untreated or microcapsule form, or may be mixed with the main agent immediately before use. Therefore, the adhesive may be a one-liquid type or a two-liquid type. In addition, the adhesive preferably contains an auxiliary agent that is one or more of a silane compound and a polyol compound. Incidentally, an adhesive in which an auxiliary is already contained in the base agent as described above (auxiliary-containing adhesive) may be used by adding and mixing a further auxiliary immediately before use.

[0026] The total amount of the auxiliary agent relative to the total amount of the adhesive used in the method according to the present embodiment may be 0.2% by mass or more and 10% by mass or less.

[0027] Specific examples of the adhesives used include WS242, WS292A, WS242A, etc. manufactured by Sika Hamatite Co., Ltd., and U-414, etc. manufactured by Dow Chemical Co., Ltd. Specific examples of the above-mentioned auxiliary agents include RC50E, MS-90, AN-1, etc. manufactured by Sika Hamatite Co., Ltd.

[0028] By using an auxiliary as described above, the adhesive strength between the adherend and the adhesive can be improved. In addition, by incorporating a primer component in the adhesive itself, a separate step of applying a primer is not required, and manufacturing efficiency can be improved. However, even when the adhesive contains an auxiliary that is a primer component, the primer may be applied to the adhesive surface of the adherend after the liquid removal process described in detail later. This further improves the adhesive strength between the adherend and the adhesive.

[0029] [Manufacturing vehicle window glass with adherend] A flow diagram of the manufacturing method of the vehicle window glass with adherend according to this embodiment is shown in Fig. 3. As shown in Fig. 3, the manufacturing method of the vehicle window glass with adherend includes a dry treatment step (S10) of dry treating the adhesive surface of the adherend, a cleaning liquid application step (S20) of applying a cleaning liquid containing one or more of water and a polar solvent to the dry-treated adhesive surface, a liquid removal step (S30) of removing the liquid on the adhesive surface, and an arrangement step (S40) of arranging the adherend on the vehicle window glass via the adhesive.

[0030] It is generally known that hydrophilic functional groups such as hydroxyl, carbonyl, and carboxyl groups can be introduced or formed on the surface of a resin by performing a dry treatment. Such hydrophilic functional groups can form chemical bonds or bonds by intermolecular forces with adhesive components in the adhesive, and contribute to improving the adhesive strength. However, depending on the material of the adherend and the conditions of the dry treatment, the adhesive strength between the adherend and the adhesive may not be improved much even if the dry treatment is performed. This is thought to be due to a weak boundary layer (WBL) that is generated on the very surface layer (near the interface) of the adherend by the dry treatment. Since the weak boundary layer is a layer that is weakly bonded to the adherend body (the bulk of the adherend), even if the adhesive and the weak boundary layer at the interface are strongly bonded, if the weak boundary layer is peeled off from the adherend body, the adhesion will be broken. In contrast, in this embodiment, two steps, a cleaning liquid application step (S20) and a liquid removal step (S30), are performed in two stages before applying the adhesive, thereby preventing the deterioration of adhesion caused by the weak boundary layer. Specifically, in the cleaning liquid application step (S20), a specific cleaning liquid is applied to the adhesive surface of the adherend to dissolve the weak boundary layer into the cleaning liquid, and then in the liquid removal step (S30), the liquid into which the weak boundary layer has dissolved is removed. This allows the weak boundary layer to be sufficiently removed, and more direct bonds are formed between the adhesive and the hydrophilic functional groups of the adherend body, resulting in improved adhesion between the adherend and the adhesive.

[0031] In this specification, "improved adhesion" or "excellent adhesion" refers to at least a high cohesive failure rate when a destructive test is performed, and also refers to an improvement in adhesive strength. The vehicle window glass with adherend obtained by this embodiment has a high cohesive failure rate when evaluated by a destructive test such as a knife cut test, and also has a high cohesive failure rate in a destructive test under more severe conditions, such as a destructive test by splitting (such as a splitting test conforming to JIS K 6853 1994). Furthermore, the above-mentioned "adhesiveness" means the adhesiveness immediately after the adhesion is formed, and also includes adhesive durability, i.e., the maintenance of excellent adhesiveness, and particularly the maintenance of excellent adhesiveness under severe environments (for example, under high temperature and / or high humidity). The adhesive durability under high temperature and / or high humidity can be evaluated, for example, by measuring the adhesive strength after immersion in hot water for a predetermined time.

[0032] Each step in the above manufacturing method will now be described in detail.

[0033] <Pretreatment process> An optional pretreatment step may be performed before the dry treatment step (S10). The pretreatment step is, for example, a step of cleaning the surface of the adherend, specifically at least the adhesive surface of the adherend. The cleaning may be performed by a known method. By cleaning, fine dust or dirt on the surface of the adherend can be physically or chemically removed in advance. If dust or dirt can be sufficiently removed from the adherend in advance, more hydrophilic functional groups can be introduced to the surface of the adherend in the subsequent dry treatment step (S10), and the adhesion can be improved.

[0034] The cleaning method is not particularly limited, but examples thereof include removing dust or dirt present on the adherend surface by mechanical force, dissolving in a solvent, decomposing by a solvent, or a combination thereof. Among the above, it is preferable to include removing by mechanical force, since cleaning can be performed efficiently. Specifically, examples include wiping, polishing, immersion in a cleaning solution, etc. When a solvent is used, it is preferable that the solvent does not denature the adherend, is capable of dissolving or decomposing dust or dirt that may be present on the adherend surface, and is volatile.

[0035] <Dry processing step (S10)> In the dry treatment step (S10), at least the adhesive surface of the adherend is treated. In the dry treatment step (S10), at least the adhesive surface of the adherend is chemically surface-modified. Specifically, hydrophilic functional groups such as hydroxyl groups, carbonyl groups, and carboxyl groups are introduced or formed, and the number of hydrophilic functional groups per unit area of ​​the adhesive surface can be increased. As described above, the hydrophilic functional groups can form chemical bonds or bonds by intermolecular forces with the adhesive components of the adhesive.

[0036] As the dry treatment, a known method used for modifying the surface of a resin can be used. The dry treatment preferably includes one or more of plasma treatment, corona treatment, flame treatment, and itro treatment, and plasma treatment is preferred because it causes relatively little damage to the adherend and has a high effect of modifying the surface of the resin. The plasma treatment is a treatment in which the surface of the adherend is irradiated with plasma. The means for generating plasma is not particularly limited, and may be a high-frequency plasma generator or a low-frequency plasma generator. In addition, plasma generated by irradiation with a laser, microwaves, or the like may be used.

[0037] The conditions for the dry treatment step (S10) can be adjusted as appropriate depending on the resin material used for the adherend, the type of adhesive, the purpose of the adherend, and the location of use in the vehicle. For example, when the resin material used for the adherend is a resin that is difficult to adhere to an adhesive, the adhesiveness can be increased by performing the dry treatment under somewhat stricter conditions. When the dry treatment is a plasma treatment, it is preferably an atmospheric plasma treatment. For example, the frequency of the applied voltage of the power source of the plasma generating means is 50 Hz or more and 2.45 GHz or less, preferably 50 Hz or more and 25 kHz or less, and the output power density is 15 W / cm. 2 More than 200W / cm 2 Less than 50W / cm, preferably 50W / cm 2 More than 100W / cm 2 The irradiation distance (the distance between the electrode and the adherend surface) is 2 mm to 10 mm, preferably 4 mm to 8 mm. The irradiation time may be 1 second to 10 seconds, preferably 2 seconds to 5 seconds. When the irradiation nozzle is moved, the nozzle movement speed may be 2.5 m / min to 10 m / min, preferably 2.5 m / min to 4 m / min.

[0038] In the dry treatment step (S10), the surface temperature of the adherend before treatment may be room temperature (23°C ± 3°C). However, the adherend may be heated to a temperature higher than room temperature, for example, to 60°C or higher, preferably 80°C or higher, more preferably 100°C or higher, even more preferably 120°C or higher, and particularly preferably 140°C or higher. By raising the surface temperature of the adherend, the introduction of the above-mentioned hydrophilic functional groups on the surface of the resin of the adherend is promoted, and the adhesion between the adherend and the adhesive in the vehicle window glass with the adherend obtained through the subsequent steps can be further improved.

[0039] <Cleaning liquid application step (S20)> After the dry treatment step (S10), the process proceeds to a cleaning liquid application step (S20) in which a cleaning liquid is applied to the dry-treated adhesive surface of the adherend. The cleaning liquid used in this step contains one or more of water and a polar solvent. The cleaning liquid may be one that has a high function of dissolving the above-mentioned weak boundary layer, preferably a liquid with high polarity. Therefore, the solubility parameter of the cleaning liquid may be 8 or more, preferably 10 or more.

[0040] The cleaning liquid may be water alone or a polar solvent alone, but from the viewpoint of WBL removal performance, a mixture of water and a polar solvent is preferred, and a mixture of water and a plurality of polar solvents is more preferred. When the cleaning liquid is a mixture of water and a polar solvent, the water and the polar solvent in the cleaning liquid can be mixed at a mass ratio of 0.1:99.9 to 80:20. For example, the cleaning liquid is preferably a mixture of water and a lower alcohol.

[0041] When the cleaning solution contains water, the water may be distilled water, ion-exchanged water, etc. Examples of polar solvents include lower alcohols such as methanol, ethanol, 2-propanol (isopropyl alcohol), and 1-propanol; ketones such as acetone, methyl ethyl ketone, and methyl isobutyl ketone; esters such as butyl acetate, ethyl acetate, and glycol ester; aliphatic or alicyclic hydrocarbons such as n-hexane and cyclohexane; and ethers such as diethyl ether and glycol ether. In addition, it is preferable that the cleaning solution contains lower alcohols, and in particular ethanol, in consideration of safety, because of its good solubility.

[0042] The cleaning liquid may also contain optional additives such as preservatives, pH adjusters, rust inhibitors, and antioxidants, as well as acid components and primer components, to the extent that the functions of the cleaning liquid are not impaired.

[0043] The method for carrying out the cleaning liquid attachment step (S20) is not particularly limited as long as it is a method that can create a state in which the cleaning liquid is sufficiently attached to the adhesive surface. Specific methods include spraying (atomizing), scattering, dripping, etc., of the cleaning liquid onto the adhesive surface. Among these, spraying is preferred because it is possible to create a state in which the cleaning liquid is evenly attached to the adhesive surface by making the cleaning liquid into a mist and contacting it with the adhesive surface, and it is easy to quantify. In addition, in the case of spraying, pressure is applied at the moment the cleaning liquid and the adherend come into contact, so that the pressure is also applied to the weak boundary layer, making it easier to dissolve into the cleaning liquid. The spraying pressure during spraying may be 0.05 MPa or more and 0.3 MPa or less. Note that the amount of cleaning liquid attached to the adhesive surface by attachment methods such as spraying, scattering, and dripping is 0.025 g / cm. 2 More than 2g / cm 2 It may be the following:

[0044] The cleaning liquid may be applied to the adhesive surface of the adherend by immersing at least the adhesive side of the adherend in the cleaning liquid. In this case, for example, the adherend is placed in a container filled with the cleaning liquid so that at least the adhesive side or the entire adherend is immersed in the cleaning liquid. With the adherend immersed in the cleaning liquid, the cleaning liquid may be caused to flow or the adherend itself may be moved. A blade agitator, ultrasonic waves, etc. may be used to cause the cleaning liquid to flow. Furthermore, the cleaning liquid may be poured over the surface of the adherend. When the cleaning liquid is poured over, the process includes a cleaning liquid application process (S20) and a liquid removal process (S30).

[0045] In the cleaning liquid application step (S20), the cleaning liquid may be applied to the adhesive surface by supplying the cleaning liquid from a fiber-containing substrate or a porous substrate that has been saturated or oversaturated with the cleaning liquid onto the adhesive surface. In this case, the substrate may be moved in the direction of the adhesive surface to spread the cleaning liquid and form a film of the cleaning liquid on the adhesive surface, but the liquid should not be wiped off during the operation. The fiber-containing substrate or porous substrate may be a lump material such as felt, cotton, or sponge, a sheet material such as cloth or nonwoven fabric, or a brush.

[0046] The above-mentioned cleaning liquid application methods may be used alone or in combination.

[0047] By carrying out this cleaning liquid application step (S20), a state in which the cleaning liquid is continuously present on the bonding surface in the surface direction can be created, and this state can be maintained for a certain period of time. The area in which the cleaning liquid is continuously present on the bonding surface may be at least the area in which the adhesive is to be disposed, but may be a range of 80% or more of the total area of ​​the bonding surface, and is preferably the entire bonding surface. In such a state in which the cleaning liquid is continuously present on the bonding surface, for example, 0.025 g / cm 2 More than 1 g / cm, preferably 1 g / cm 2 The cleaning liquid may be present in an amount of 100 μm or more. Alternatively, a film or layer of the cleaning liquid may be present on the adhesive surface with a thickness of 25 μm or more, preferably 100 μm or more. In addition, after the cleaning liquid is applied to the adherend in the cleaning liquid application step (S20), the adherend may be left for a predetermined time until the next liquid removal step (S30). The leaving time may be 1 second or more and 8 hours or less, preferably 5 seconds or more and 60 seconds or less. For example, when the cleaning liquid is applied by spraying, the leaving time is the time from the completion of spraying to the start of the liquid removal step (S30), and when the cleaning liquid is applied by immersion, the leaving time is the time from the removal of the adherend from the liquid tank containing the cleaning liquid to the start of the liquid removal step (S30).

[0048] Thus, in the cleaning liquid attachment step (S20) of the present embodiment, the cleaning liquid can be in contact with the adhesive surface of the adherend for a longer period of time than in the conventional method. Therefore, the weak boundary layer on the adhesive surface of the adherend is exposed to a sufficient amount of cleaning liquid for a long period of time. This helps dissolution of the weak boundary layer into the cleaning liquid, and more of the weak boundary layer can detach from the adherend body.

[0049] The cleaning solution application step (S20) is preferably carried out at 35° C. or below, and more preferably at room temperature, in order to prevent the cleaning solution from volatilizing.

[0050] The cleaning liquid application step (S20) may be performed once or multiple times. When performing the cleaning liquid application step multiple times, the same method may be repeated multiple times, or a different cleaning liquid application method may be used for each time.

[0051] <Liquid removal process (S30)> After the cleaning liquid application step (S20), the liquid adhering to the adhesive surface is removed in a liquid removal step (S30). The specific method of removal is not particularly limited, but examples include wiping the liquid with a substrate, allowing the substrate to soak in the liquid, blowing the liquid off, etc. These methods may be used alone or in combination.

[0052] When the liquid is wiped off with a substrate or when the liquid is soaked into the substrate, the substrate may be a substrate containing fibers or a porous substrate, for example, a lump material such as felt, cotton, or sponge, a sheet-like material such as cloth or nonwoven fabric, or a brush. The liquid removal step (S30) is preferably performed using a substrate in a dry state or a substrate that has been subjected to a drying treatment. The substrate may contain some liquid, but the substrate has a function of absorbing and removing the liquid present on the adhesive surface. That is, the substrate used in the liquid removal step (S30) is in a liquid-unsaturated state or has a liquid-absorbing ability. In addition, when wiping off the liquid, a pressure of 10 Pa to 1000 Pa is applied, and the liquid can be wiped off at a speed of 1 mm / sec to 1000 mm / sec.

[0053] When blowing off the liquid, an air blower (air knife) or the like can be used. The pressure when blowing off may be 0.05 MPa or more and 0.5 MPa or less.

[0054] In the liquid removal step (S30), the liquid may be wiped off using a substrate that does not have liquid absorption capacity, other than the above-mentioned substrate containing fibers or porous substrate.

[0055] In the liquid removal step (S30), the liquid in the state in which the weak boundary layer has dissolved in the cleaning liquid after the cleaning liquid application step (S20) is removed, so that the weak boundary layer can be removed from the adhesive surface of the adherend. As a result, when the adhesive is placed on the adherend, the adhesive comes into direct contact with the adherend body, and the hydrophilic functional groups of the adherend body and the adhesive components can bond more reliably.

[0056] The liquid removing step (S30) may also be performed once or multiple times. When performing multiple times, the same method may be repeated multiple times, or a different method may be used for each time. After performing the cleaning liquid applying step (S20) and the liquid removing step (S30), the cleaning liquid applying step (S20) and the liquid removing step (S30) may be further repeated.

[0057] <Placement process (S40)> After the liquid removing step (S30), the process proceeds to a placing step (S40) in which the adherend is placed on the vehicle window glass via an adhesive. In the placing step (S40), the adhesive is applied to the adhesive surface of the adherend, and then the adherend with the adhesive is attached to the vehicle window glass so that the adhesive surface of the adherend faces the main surface of the vehicle window glass. Alternatively, the adhesive is applied to a predetermined location in the intended facing region of the adherend on the main surface of the vehicle window glass, and then the adhesive surface of the adherend is made to face the vehicle window glass and attached to the intended facing region. As shown in Figs. 1 and 2, when a shielding layer 15 is formed on the main surface of the glass plate 11 on the vehicle interior side of the vehicle window glass 10, it is preferable to place the adherend 30 on the shielding layer 15 via an adhesive 20.

[0058] The method of applying the adhesive is not particularly limited. For example, a dedicated tool depending on the type of adhesive can be used.

[0059] A primer specifically for glass may be applied to the opposing surface of the vehicle window glass at least in the area where the adhesive is to be placed, and a primer may also be applied separately to the adhesive surface of the adherend after the liquid removal step (S30). However, in this embodiment, since high adhesion is obtained by the above-mentioned steps, it is preferable that the application of one or both of the primers can be omitted, simplifying the manufacturing process.

[0060] <Curing process> After the placement step (S40), the structure in which the adherend and the vehicle window glass are attached via the adhesive can be stored, that is, cured, in a predetermined environment. Curing promotes hardening of the adhesive, and can increase the adhesive strength. The curing conditions vary depending on the material of the adherend, the type of adhesive, the conditions of each of the above-mentioned steps, and the like, but can be, for example, cured at a temperature of 5 to 35°C and / or a humidity of 20 to 80% RH. Note that curing can also be performed at a temperature above room temperature by directly or indirectly heating the adhesive, etc. EXAMPLES

[0061] Hereinafter, the embodiment of the present invention will be described in more detail based on examples.

[0062] [Experimental example 1: Test using test pieces] A glass plate with an adherend was prepared using the plate-shaped test piece as an adherend, and the adhesiveness was evaluated.Of the following examples, Examples 1-1 to 1-7 are working examples, and Examples 1-8 to 1-11 are comparative examples.

[0063] (Example 1-1) =Preprocessing= A test piece (25 mm × 150 mm, thickness 0.5 mm, adhesive surface area 250 mm) was cut from a flat molded polyamide (PA) body. 2 Then, a nonwoven fabric wiper (Bencott (registered trademark) manufactured by Asahi Kasei Corporation) was soaked in hexane (Sigma-Aldrich Japan LLC, special grade reagent), and the adhesive surface of the bracket was wiped and cleaned with the nonwoven fabric wiper.

[0064] = Dry processing process = Thereafter, the adhesive surface of the test piece was subjected to plasma treatment using a plasma treatment device (Wedge Corporation, atmospheric plasma irradiation surface modification device "PS-601SW"). The conditions for the plasma treatment were device output (frequency of the applied voltage of the power supply) of 60 Hz, output power of 600 W (output power density of 50 W / cm 2 ), irradiation distance (distance between the test piece and the radiation nozzle) was 5 mm, and irradiation time was 5 seconds.

[0065] =Cleaning solution application process= After the plasma treatment, 30 g of distilled water was mixed with 70 g of mixed ethanol (Yamaichi Chemical Industry's "Mixed Ethanol NP", a mixture of 80-90% by mass of ethanol, 5-10% by mass of 1-propanol, and isopropyl alcohol) to prepare a cleaning liquid. The cleaning liquid was filled into a spray bottle. The test piece was placed on a horizontal table with the adhesive surface facing up, and the above cleaning liquid was sprayed onto the entire adhesive surface of the test piece. The spray pressure was 0.1 MPa, and the amount of cleaning liquid used for spraying was 0.5 mL. The cleaning liquid adhesion treatment was performed at room temperature (23°C ± 3°C).

[0066] =Liquid removal process= Thereafter, the liquid adhering to the test piece was wiped off with a nonwoven wiper ("Bencotto M-1" manufactured by Asahi Kasei Corporation). The wiper used for wiping was unused and dry. Wiping was performed in one direction, once in one direction, at a speed of 10 mm / sec, applying a force of 500 Pa. After spraying of the cleaning liquid (after the cleaning liquid adhesion treatment), the test piece was left for 30 seconds before wiping began, and the wiping time was 1 second. The wiping treatment was also performed at room temperature (23°C ± 3°C).

[0067] =Placement process= After the liquid was removed, a urethane adhesive (WS292A manufactured by Sika Hamatite) was applied to the adhesive surface of the test piece using a dedicated application gun so that an adhesive layer of 1.0 mm thickness was formed over 80% of the area of ​​the adhesive surface in a plan view. In addition, a glass plate (100 mm x 100 mm) on which a shielding layer (black ceramic layer) was formed was prepared. The test piece on which the adhesive was applied was placed on the glass plate, facing the main surface of the shielding layer side of the glass plate, with the adhesive interposed between them. The obtained structure was cured for 7 days at 23°C ± 3°C and 50-70% RH, to obtain a glass plate with a test piece attached.

[0068] (Example 1-2) A glass plate with a test piece was obtained in the same manner as in Example 1-1, except that a resin primer ("RC-50E" manufactured by Sika Hamatite) was applied and then a urethane-based adhesive ("WS292A" manufactured by Sika Hamatite) was used.

[0069] (Example 1-3) A glass plate with a test piece was obtained in the same manner as in Example 1-1, except that the adhesive used in Example 1-1 was replaced with an adhesive made by mixing a urethane adhesive ("WS242" manufactured by Sika Hamatite) and a polyol hardener ("AN-1" manufactured by Sika Hamatite) in a ratio of 90:10.

[0070] (Example 1-4) A glass plate with a test piece was obtained in the same manner as in Example 1-1, except that the washing liquid was changed to distilled water.

[0071] (Example 1-5) A glass plate with a test piece was obtained in the same manner as in Example 1-1, except that the cleaning liquid was changed to one consisting only of the above-mentioned mixed ethanol.

[0072] (Example 1-6) A glass plate with a test piece was obtained in the same manner as in Example 1-1, except that the cleaning liquid was changed to isopropanol (IPA).

[0073] (Example 1-7) A glass plate with a test piece was obtained in the same manner as in Example 1-1, except that the test piece had the same shape as the test piece in Example 1-1 but was made of polybutylene terephthalate (PBT).

[0074] (Example 1-8) After the "dry treatment step", a wet wiping process was carried out instead of the "cleaning solution application step" and the "liquid removal step". Specifically, a nonwoven wiper ("Bencott M-1" manufactured by Asahi Kasei Corporation) was soaked in 0.5 mL of the same cleaning solution as in Example 1-1, and the adhesive surface of the test piece was wiped in one direction, once in one direction, at a speed of 10 mm / sec while applying a force of 500 Pa. The wiping took 1 second. Thereafter, a glass plate with a test piece was obtained in the same manner as in Example 1-1.

[0075] (Example 1-9) A glass plate with a test piece was obtained in the same manner as in Example 1-8, except that the liquid for dipping the nonwoven fabric wiper was changed to distilled water.

[0076] (Example 1-10) A glass plate with a test piece was obtained in the same manner as in Example 1-8, except that the test piece had the same shape as the test piece in Example 1-8 but was made of polybutylene terephthalate (PBT).

[0077] (Example 1-11) A glass plate with a test piece was obtained in the same manner as in Example 1-1, except that after the "dry processing step", the test piece was placed on the glass plate without carrying out the "cleaning liquid application step" and the "liquid removal step".

[0078] <Adhesion evaluation> The adhesion of the glass plate with the test piece obtained in each example was evaluated by a cleavage test conforming to JIS K 6853 1994. Figures 4(a) to 4(c) are diagrams for explaining the apparatus and method of the cleavage test used in the examples. For the test, a cleavage test apparatus 80 as shown in Figures 4(a) to 4(c) was used. The apparatus 80 is configured so that the glass plate with the adherend to be tested is attached between the first support part 81 on the upper side and the lower base 84 on the lower side, and then the first support part 81 and the second support part 82 provided on the lower base 84 can be moved in a direction in which they are relatively separated in the vertical direction. In this test, the upper surface of the test piece 130 of the glass plate with the test piece 100 obtained in each example was fixed to the first support part 81, and the lower surface of the glass plate 110 was fixed to the lower base 84 on which the second support part 82 was provided (Figure 4(a)). Then, the first support portion 81 and the second support portion 82 were moved away from each other in the vertical direction (thickness direction of the glass plate) at a speed of 50 mm / sec, thereby fracturing the glass plate 100 with the test piece (FIGS. 4(b) and (c)).

[0079] After the glass plate 100 with the test piece was cleaved, the state of the adhesive surface of the test piece was visually observed, and the percentage of the area where the adhesive 120 had undergone cohesive failure was recorded as the cohesive failure rate (CF rate, unit %). A CF rate of 0% means that the adhesive has not undergone cohesive failure at all and interfacial peeling has occurred, and a CF rate of 100% means that the adhesive has undergone cohesive failure over the entire surface applied. The higher the CF rate, the greater the percentage of cohesive failure in the adhesive, and the better the adhesiveness can be evaluated. This cleavage test was performed at room temperature (23°C ± 3°C), and also after the same example of the glass plate with the test piece had been immersed in hot water at 80°C for 150 hours (after hot water immersion). The results are shown in Table 1.

[0080] [Table 1]

[0081] As shown in Table 1, in Examples 1-1 to 1-7, the CF ratio at room temperature was 100%, and the CF ratio after hot water immersion was 80% or more. It was found that the examples (Examples 1-1 to 1-7) in which a cleaning liquid application step of applying a cleaning liquid to the adhesive surface of the dry-treated test piece and a liquid removal step of removing the liquid on the adhesive surface were performed showed superior adhesion to the examples (Examples 1-8 to 1-10) in which the cleaning liquid application step and the liquid removal step were not performed, and the example in which no liquid treatment was performed at all (Example 1-11).

[0082] [Experimental Example 2: Test using brackets] Furthermore, a glass plate with an adherend was produced using a bracket, which is a practical product, as the adherend, and the adhesiveness was evaluated.Of the following examples, Examples 2-1 to 2-7 are working examples, and Examples 2-8 to 1-10 are comparative examples.

[0083] (Example 2-1) =Preprocessing= Polyamide (PA) camera sensor bracket (total length 70 mm, width 50 mm, adhesive surface area approx. 2000 mm 2 A hexagonal shape with a roughly circular opening was prepared. A nonwoven fabric wiper (Bencott (registered trademark), Asahi Kasei Corporation) was soaked in hexane (Sigma-Aldrich Japan, LLC, special grade reagent), and the adhesive surface of the bracket was wiped and cleaned with the nonwoven fabric wiper.

[0084] = Dry processing process = Thereafter, the adhesive surface of the bracket was subjected to plasma treatment using the same plasma device as that used in [Experimental Example 1]. The conditions of the plasma treatment were also the same as those in [Experimental Example 1].

[0085] =Cleaning solution application process= After the plasma treatment, 100 g of distilled water was mixed with 400 g of mixed ethanol (Yamaichi Chemical Industry's "Mixed Ethanol NP", a mixture of 85% by mass of ethanol, 10% by mass of 1-propanol, and 5% by mass of isopropyl alcohol) to prepare a cleaning liquid. The cleaning liquid was filled into a spray bottle. The bracket was placed on a horizontal table with the adhesive surface facing up, and the above cleaning liquid was sprayed onto the entire adhesive surface of the bracket. The spray pressure was 0.15 MPa, and the amount of cleaning liquid used for spraying was 2 mL. The cleaning liquid was applied at room temperature (23°C ± 3°C).

[0086] =Liquid removal process= The liquid adhering to the bracket was then wiped off with a nonwoven wiper ("Bencotto M-1" manufactured by Asahi Kasei Corporation). The wiper used for wiping was unused and dry. Wiping was performed in one direction, once in one direction, at a speed of 40 mm / sec, with a force of 500 Pa applied. After spraying of the cleaning liquid was completed (after the cleaning liquid application step), the bracket was left for 30 seconds before wiping began, and the wiping time was 4 seconds. The liquid removal step was also performed at room temperature (23°C ± 3°C).

[0087] =Placement process= After the liquid was removed, a resin primer ("RC-50E" manufactured by Sika Hamatite) was applied to the adhesive surface of the bracket, and then a urethane adhesive ("WS292A" manufactured by Sika Hamatite) was applied using a dedicated application gun so that an adhesive layer of 1.0 mm thickness was formed over 80% of the area of ​​the adhesive surface in a plan view. In addition, a glass plate (100 mm x 100 mm) on which a shielding layer (black ceramic layer) was formed was prepared. The bracket with the adhesive applied to its adhesive surface was placed on the glass plate, facing the main surface of the shielding layer side of the glass plate, with the adhesive interposed between them. The obtained structure was cured for 7 days at 23°C ± 3°C and 50-70% RH to obtain a glass plate with a bracket.

[0088] (Example 2-2) A glass plate with brackets was obtained in the same manner as in Example 2-1, except that after spraying of the cleaning liquid (after the cleaning liquid application step), the time left for 120 seconds before wiping was started was changed.

[0089] (Example 2-3) A glass plate with brackets was obtained in the same manner as in Example 2-1, except that the spraying of the cleaning liquid (cleaning liquid application process) was repeated twice, i.e., the processes were performed in the following order: "dry processing process", "cleaning liquid application process", a second "cleaning liquid application process", "liquid removal process" and "placement process".

[0090] (Example 2-4) A glass plate with brackets was obtained in the same manner as in Example 2-1, except that the "cleaning liquid application step" and the "liquid removal step" were repeated twice, i.e., the processing was performed in the following order: "dry processing step," "cleaning liquid application step," "liquid removal step," a second "cleaning liquid application step," a second "liquid removal step," and the "placement step."

[0091] (Example 2-5) A glass plate with a bracket was obtained in the same manner as in Example 2-1, except that the method of the "cleaning liquid application step" was changed. Specifically, after the "dry processing step", the bracket was placed in a liquid tank filled with the same cleaning liquid as in Example 2-1 so that the entire bracket was immersed, and left for 300 seconds. In addition, the time from the cleaning liquid application step to the start of the liquid removal step was 60 seconds. After the bracket was removed from the liquid tank, the "liquid removal step" and "positioning step" were performed in the same manner as in Example 2-1.

[0092] (Example 2-6) A glass plate with brackets was obtained in the same manner as in Example 2-1, except that the method of the "liquid removal step" was changed. Specifically, after the "cleaning liquid attachment step" was performed in the same manner as in Example 2-1, air was applied using an air blowing device ("Air Tool Series" manufactured by Kurita Manufacturing Co., Ltd.) at a blowing distance of 50 cm for a blowing time of 10 seconds to blow off the liquid adhering to the adhesive surface of the bracket. Then, the "placement step" was performed in the same manner as in Example 2-1.

[0093] (Example 2-7) A glass plate with brackets was obtained in the same manner as in Example 2-1, except that the method of the "liquid removal step" was changed. In this example, after the "cleaning liquid application step" was performed in the same manner as in Example 2-1, a nonwoven fabric wiper ("Bencotto M-1" manufactured by Asahi Kasei Corporation) was spread, and the bracket was placed on it with the adhesive side of the bracket facing down, and left for 1 second to transfer and remove the cleaning liquid. Then, the "placement step" was performed in the same manner as in Example 2-1.

[0094] (Example 2-8) After the plasma treatment, a wet wiping process was performed instead of the "cleaning solution application process" and the "liquid removal process". Specifically, a nonwoven wiper ("Bencott M-1" manufactured by Asahi Kasei Corporation) was soaked in 0.5 mL of the same cleaning solution as in Example 2-1, and the adhesive surface of the bracket was wiped in one direction, once in one direction, at a speed of 40 mm / sec while applying a force of 500 Pa. The wiping took 4 seconds. A glass plate with a bracket was obtained in the same manner as in Example 2-1.

[0095] (Example 2-9) A glass plate with brackets was obtained in the same manner as in Example 2-1, except that after the "dry processing step", the brackets were placed on the glass plate without carrying out the "cleaning liquid application step" and the "liquid removal step".

[0096] (Example 2-10) A glass plate with brackets was obtained in the same manner as in Example 2-1, except that the "dry processing step," "cleaning liquid application step," and "liquid removal processing step" were not performed, and the brackets were placed on the glass plate immediately after the "pretreatment."

[0097] The bracket-attached glass plates obtained in Examples 2-1 to 2-10 were evaluated for adhesiveness by the same test method as in [Experimental Example 1]. The results are shown in Table 2.

[0098] [Table 2]

[0099] As shown in Table 2, in Examples 2-1 to 2-7, the CF ratio at room temperature was 100%, and the CF ratio after hot water immersion was 70% or more. It was found that the examples (Examples 2-1 to 2-7) in which a cleaning liquid application process in which a cleaning liquid was applied to the adhesive surface of the dry-processed bracket and a liquid removal process in which the liquid on the adhesive surface was removed were subjected to showed superior adhesion to the example (Example 2-8) in which the cleaning liquid application process and the liquid removal process were not performed, and the examples in which no liquid treatment was performed at all (Examples 2-9 and 2-10).

[0100] As described above, it has been found that the present invention can provide a method for producing a vehicle window glass with an adherend, which exhibits excellent adhesion between the adherend and the adhesive even under harsher environments. [Explanation of symbols]

[0101] 1 Vehicle window glass with substrate 10 Window glass (laminated glass) 11, 12, 110 Glass plate 13 Interlayer 15 Shielding layer 20, 120 Adhesive 30 Adherent 80 Splitting tester 81 1st support part 82 Second support part 84 Lower stand 100 Glass plate with test pieces 130 Test Piece

Claims

1. A method for producing a vehicle window glass with an adherend, in which an adherend having a resin surface and a vehicle window glass are bonded together via an adhesive, comprising the steps of: Dry-treating the adhesive surface of the adherend; A cleaning solution containing at least one of water and a polar solvent is applied to the dry-treated adhesive surface; removing the liquid on the adhesive surface; and disposing the adherend on the vehicle window glass via an adhesive.

2. The manufacturing method according to claim 1 , wherein the application of the cleaning liquid includes at least one of spraying and sprinkling the cleaning liquid on the dry-treated adhesive surface and immersing at least the adhesive surface side of the adherend in the cleaning liquid.

3. The method according to claim 1 or 2, wherein removing the liquid comprises one or more of wiping the liquid with a dry substrate, allowing the liquid to soak into the substrate, and blowing the liquid off.

4. The method according to claim 1 , wherein the cleaning solution has a solubility parameter of 8 or more.

5. The method according to claim 4 , wherein the cleaning liquid is a mixture of water and a lower alcohol.

6. The method according to claim 1 or 2, wherein the resin comprises one or more of polyamide, polyester, polyacetal, polycarbonate, modified polyphenylene ether, and epoxy.

7. The method according to claim 1 or 2, wherein the dry treatment comprises one or more of a plasma treatment, a corona treatment, a flame treatment and an itro treatment.

8. The manufacturing method according to claim 1 or 2, wherein the adhesive is a moisture-curing adhesive.

9. The method of claim 8 , wherein the adhesive contains an auxiliary agent which is one or more of a silane compound and a polyol compound.

10. The manufacturing method according to claim 1 or 2, wherein the adherend is a bracket for mounting an in-vehicle device.

11. The manufacturing method according to claim 1 or 2, wherein a shielding layer is formed on a main surface of the vehicle window glass, and the adherend is disposed on the shielding layer via the adhesive.

Citation Information

Patent Citations

  • Manufacturing method for laminate

    JP2019084520A